2011
DOI: 10.3758/s13423-011-0107-8
|View full text |Cite
|
Sign up to set email alerts
|

Scene context influences without scene gist: Eye movements guided by spatial associations in visual search

Abstract: Although the use of semantic information about the world seems ubiquitous in every task we perform, it is not clear whether we rely on a scene's semantic information to guide attention when searching for something in a specific scene context (e.g., keys in one's living room). To address this question, we compared contribution of a scene's semantic information (i.e., scene gist) versus learned spatial associations between objects and context. Using the flash-previewmoving-window paradigm Castelhano and Henderso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
123
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 31 publications
7
123
4
Order By: Relevance
“…Recent studies have reported that the global information of a scene (e.g., gist or layout) can influence visual search (e.g., Castelhano & Heaven, 2011;Castelhano & Henderson, 2007;Torralba, Oliva, Castelhano, & Henderson, 2006;Võ & Henderson, 2010). For example, Võ and Henderson suggested that scene representations generated from only a brief glimpse of a whole scene may provide sufficient information to guide gaze during an object search.…”
mentioning
confidence: 99%
“…Recent studies have reported that the global information of a scene (e.g., gist or layout) can influence visual search (e.g., Castelhano & Heaven, 2011;Castelhano & Henderson, 2007;Torralba, Oliva, Castelhano, & Henderson, 2006;Võ & Henderson, 2010). For example, Võ and Henderson suggested that scene representations generated from only a brief glimpse of a whole scene may provide sufficient information to guide gaze during an object search.…”
mentioning
confidence: 99%
“…Their findings showed that an inconsistent object was fixated on earlier and for a longer duration than a consistent object, though attempts to replicate this finding have had mixed results [12 -15]. When the task is to search for objects that might be semantically consistent or inconsistent with scene context, attention is not initially drawn to inconsistent targets [6,16] but response times are longer. Both of the studies showing this result limited visibility of the scene to a small window during search; we could find no studies that investigated the speed of searching for semantically inconsistent targets in fully visible scenes, and so the influence of semantic consistency on guidance of later stages of search is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In two studies that manipulated the plausibility of target locations in scenes, objects that appeared in likely locations were found more quickly than targets that appeared in unlikely locations, even though the use of windowed viewing during search meant that detailed scene syntax could only be derived during the preview of the scene [6,16]. Another study used fully visible scenes, and showed that the first saccade during search landed closer to the likely target location than to the unlikely target location, when the target was both present and absent [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations